2020
DOI: 10.3390/diagnostics10121022
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Pharmacologic and Rehabilitative Treatment of Small Fiber Neuropathies

Abstract: The aim of this systematic review is to guide the physician in defining the pharmacologic and rehabilitative therapeutic approaches for adopting the best strategies described in the current literature. The search was conducted in PubMed, EMBASE, Cochrane Library and Web of Science to identify the treatment of small fiber neuropathies. Two reviewers independently reviewed and came to a consensus on which articles met inclusion/exclusion criteria. The authors excluded the duplicates, animal studies and included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Second, SFN is typically chronic and challenging to treat. 23,24 Thus, recognizing SFN may help clinicians and patients anticipate a prolonged clinical course for which a multidisciplinary approach to management (e.g., neurologists, pain specialists, physical, and occupational therapists) may be beneficial in improving the quality of life and functional status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Second, SFN is typically chronic and challenging to treat. 23,24 Thus, recognizing SFN may help clinicians and patients anticipate a prolonged clinical course for which a multidisciplinary approach to management (e.g., neurologists, pain specialists, physical, and occupational therapists) may be beneficial in improving the quality of life and functional status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neither drugs in therapy or prevention have succeeded in ameliorating sharply neuropathic symptoms and pain, nor quantitative assessment of neuropathy has been authorized or approved so far. Nevertheless, since taxanes and platinum salts are known to hit first small autonomic C-fibers, some efforts have been made to quantify neuropathic damagein the early steps of the anticancer treatment [ 133 , 198 , 199 , 200 ]. Recently, a sudomotor function testing has been suggested to screen early peripheral neuropathy, on the basis that sweat glands are innervated by small C-fibers,.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a sudomotor function testing has been suggested to screen early peripheral neuropathy, on the basis that sweat glands are innervated by small C-fibers,. Other assessment tools have already been reported in literature [ 198 , 199 , 200 ]: skin biopsy to determine the intradermal nerve fiber density and innervated skin structure; corneal confocal microscopy to quantify small nerve fibers in the cornea; sympathetic skin response, measured the unmyelinated nerve sudormotor function after a transient change in electrical skin potential; axon flare reflex tests, evidencing the hyperemic response of the axons; pain-related evoked potentials to assess the nociceptive system. …”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of SFN will allow for an objective measurement of the effects of interventions and the information provided by the skin biopsies will further research on the inflammatory and immunological processes involved. Additionally, studies have shown improvement with specific rehabilitative treatments in SFN and this body of work may prove equally applicable to those with FM [ 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%